ANALISIS MOTIVASI KERJA DOSEN STAI ANNUR LAMPUNG SELATAN - Riyuzen - (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2018)
High quality of graduates, complete facilities and infrastructure, effective learning system,reliable lecturers, competitive pricing / cost of education and strategic campus location have notguaranteed the existence and development of a private Islamic university. Organizational culture istherefore expected to follow, select and innovate the changes.The result of the research shows the correlation between the two variables of organizationalculture on the motivation of lecturer in STAI Annur, Lampung Selatan. The positive direction ofrelationship indicates that the existence of good relation and influence of organizational culture willmake the motivation of lecturer in STAI Annur Lampung Selatan increasing.